Evektifitas Model Pembelajaran Make A Match Terhadap Keterampilan Berpikir Kritis Pada Mata Pelajaran Geografi Kelas X di SMA Negeri 2 Palu - Ardayanti Ardayanti; Ika Listiqowati; Exsa Putra; Nurvita Nurvita; Olvi Yuliana (LPPM Institut Pendidikan Nusantara Global, 2026)
Critical thinking skills are essential skills that students must develop. This study aims to test the effectiveness of the “Make a Match” learning model on the critical thinking skills of 10th-grade students at SMA Negeri 2 Palu. This study employs a quantitative approach using a quasi-experimental design with a Nonequivalent Control Group Design. The study population consisted of 60 students, while the sample comprised 30 students selected from class X-F as the experimental group and class X-C as the control group. The research instrument consisted of multiple-choice tests administered as pretests and posttests. The research data were analyzed using normality, homogeneity, and hypothesis tests with the assistance of SPSS version 25 software. The results of the study indicate an improvement in critical thinking skills, as evidenced by the highest score of 91 and the average posttest score of the experimental class (79.50), which was higher than that of the control class (61.86). The results of the hypothesis test yielded a significance value (2-tailed) of 0.000 < 0.05, indicating a significant effect of the Make a Match learning model on students’ critical thinking skills. The limitations of this study lie in the fact that it was conducted over a limited timeframe and focused exclusively on remote sensing; consequently, the results cannot yet be generalized to other areas of geography. Further research is recommended over a longer period and across different geographical subjects to more broadly assess the effectiveness of the learning model.